Synthetic Method and Oil Displacement Capacity of Nano-MoS2. (13th July 2022) - Zhang, Liang; Zhou, Fujian; Lei, Guofa; Ge, Bingyu; Li, Yuan; Yu, Guolin; Zhao, Longhao; Li, Bojun; Yao, Erdong
Abstract : Nanomaterials can be used to emulsify and reduce the fluid viscosity, reduce pore pressure, and increase injection volume. Therefore, nanomaterials have a great potential in the enhanced oil recovery. However, the current research on nanooil flooding materials mostly focuses on the evaluation of the oil-displacing effect, and the lack of research on the size of the oil-displacing materials for tight oil is obvious. In this work, 1T phase molybdenum disulfide nanosheets were prepared by one-step hydrothermal method, which were further modified with CTAB powders to obtain MoS2 -CTAB nanosheet powders. Combined with SEM, TEM, and AFM methods, the nanosheets were optimized based on the appearance and morphology. The stability, wetting reversal, and oil displacement capacity of selected nanosheets were tested. The results show that the best experimental condition to synthesize small-sized molybdenum disulfide is 200°C in the weak acid environment through 12 h. Due to the steric hindrance effect of the CATB molecule, the size and interlayer gap of MoS2 nanosheets increased slightly after modification. The layer gap reaches to 0.7 nm, and the number of stacked layers is 3~4 layers. Strong Raman bands are observed at 137 cm -1, 291 cm -1, and 391 cm -1, which indicates that the synthesized product is 1T MoS2 . The modified MoS2 nanosheets in aqueous solution have better dispersion than the unmodified one. After the Zeta test, it was found that the absolute value after modification became lower, indicating that the modification of nano-MoS2 was effective. Moreover, the MoS2 -CTAB can complete the wetting reversal within 4 h and make the interfacial tension reach 0.89 mN/m at 0.005 wt%, which greatly reduces the capillary pressure. The enhanced oil recovery effect of MoS2 -CTAB nanosheets increased by 85.7% compared with that before modification and 62.5% higher compared with pure surfactant.